2021
DOI: 10.3390/jpm11090907
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study of the Osteoporotic Spine Fracture: Optical Approach

Abstract: Background and objectives: Osteoporotic spine fractures represent a significant factor for decreasing quality of life in the elderly female population. Understanding the mechanisms involved in producing these fractures can improve their prevention and treatment. This study presents a biomechanical method to produce a vertebral fracture, conducted on a human spine segment, observing the displacements and strains in the intervertebral disc, endplate, and vertebral body. Materials and Methods: We performed two te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In our study, this type of fracture showed a very good evolution of the healing of both the fracture and the OBF; in all cases, only cables were used to fix them, and it was not necessary to supplement the fixation with plates. These good results were confirmed by data from the literature reporting 100% fracture and OBF healing [31][32][33].…”
Section: Discussionsupporting
confidence: 66%
“…In our study, this type of fracture showed a very good evolution of the healing of both the fracture and the OBF; in all cases, only cables were used to fix them, and it was not necessary to supplement the fixation with plates. These good results were confirmed by data from the literature reporting 100% fracture and OBF healing [31][32][33].…”
Section: Discussionsupporting
confidence: 66%
“…The model was discretized (meshed) and its constraints and loads were applied (Figure 8a). As this analysis was aimed at the intraoperative creation of the osteotomy wedge, the value of the applied force was 175 N. The value was chosen taking into account the values existing in the literature between 120-200 N [36,41]. Figure 8b shows the meshed geometric model to which the constraints and loads were applied.…”
Section: Fem Analysis For Optimization Of Owhto Geometrical Planningmentioning
confidence: 99%
“…It is worth noting the usefulness of the computer-aided approach to CAD-CAM methods of medical aspects through the superior possibilities of processing the results obtained on virtual models. Such biomechanical approaches are present in the literature [41,42].…”
Section: Owhto Geometric Planning Optimizationmentioning
confidence: 99%
“…The worldwide incidence of OVCF was estimated to be 1.4 million per year [ 3 ], which most often involved thoracolumbar spine [ 4 ]. Biomechanical modeling has revealed that the junction of thoracic and lumbar spine yields mechanical stress on different patterns of loading [ 5 9 ], thus increasing the risk of thoracolumbar OVCF (TL-OVCF). On the other hand, mechanical support from rib cage and paravertebral muscles might help to reduce the risk of non-thoracolumbar OVCF (nTL-OVCF) in middle thoracic and lower lumbar spine [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical modeling has revealed that the junction of thoracic and lumbar spine yields mechanical stress on different patterns of loading [ 5 9 ], thus increasing the risk of thoracolumbar OVCF (TL-OVCF). On the other hand, mechanical support from rib cage and paravertebral muscles might help to reduce the risk of non-thoracolumbar OVCF (nTL-OVCF) in middle thoracic and lower lumbar spine [ 5 , 9 , 10 ]. In addition to bone fragility and mechanical stress, evidence accumulates that OVCF are associated with multiple risk factors ranging from aging, female gender, comorbidity of cardiovascular and cerebrovascular diseases, to life styles such as chronic smoking and alcohol consumption [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%